2021
DOI: 10.26848/rbgf.v14.3.p1767-1786
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização do estado de conservação das estradas rurais na bacia do Ribeirão Paraíso, Jataí-GO

Abstract: As estradas são muito importantes em vários aspectos, não só importantes, mas também necessárias. Possibilitam o tráfego de pessoas em busca de necessidades básicas (saúde, educação, lazer, trabalho, etc.) como também às atividades agrícolas. Portanto, o objetivo principal desse capítulo foi caracterizar e analisar o estado de conservação das estradas rurais na bacia hidrográfica do Ribeirão Paraíso, Jataí-GO, esperando contribuir com incentivo e conscientização por parte da gestão da estrada da necessidade de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In previous research, Souza and Cunha (2021) found that the sugarcane crop significantly influences the increase in rural roads in the RPW for production flow. Therefore, the time frame of 2005, 2010, 2015, and 2020 was chosen for analysis.…”
Section: Data Acquisitionmentioning
confidence: 94%
“…In previous research, Souza and Cunha (2021) found that the sugarcane crop significantly influences the increase in rural roads in the RPW for production flow. Therefore, the time frame of 2005, 2010, 2015, and 2020 was chosen for analysis.…”
Section: Data Acquisitionmentioning
confidence: 94%